THE FORMATION OF A GREEN INVESTMENT ENVIRONMENT AND THE IMPORTANCE OF ITS MANAGEMENT - TO‘RAYEV , JASURALI (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the formation of a green investment environment, its key factors, and the importance of effective management mechanisms. It highlights the significant role of green investments in ensuring environmental sustainability in the modern economy, rational use of natural resources, and addressing climate change-related challenges. The study examines the role of public policy, financial instruments, innovative technologies, and international experience in the development of a green investment environment. It also substantiates the opportunities to enhance economic efficiency, ensure environmental safety, and achieve social well-being through effective management of these investments. The article develops practical proposals and recommendations for improving the green investment environment in the context of Uzbekistan.